Live-cell imaging of endocytosed synaptophysin around individual hippocampal presynaptic active zones - Tanaka, Hiromitsu; Funahashi, Junichiro; Hirano, Tomoo (Frontiers in Cellular Neuroscience, 2023)
In presynaptic terminals 4 types of endocytosis, kiss-and-run, clathrin-mediated, bulk and ultrafast endocytosis have been reported to maintain repetitive exocytosis of neurotransmitter. However, detailed characteristics and relative contribution of each type of endocytosis still need to be determined. Our previous live-cell imaging study demonstrated individual exocytosis events of synaptic vesicle within an active-zone-like membrane (AZLM) formed on glass using synaptophysin tagged with a pH-sensitive fluorescent protein. On the other hand, individual endocytosis events of postsynaptic receptors were recorded with a rapid extracellular pH exchange method. Combining these methods, here we live-cell imaged endocytosed synaptophysin with total internal reflection fluorescence microscopy in rat hippocampal culture preparations. Clathrindependent and -independent endocytosis, which was seemingly bulk endocytosis, occurred within several seconds after electrical stimulation at multiple locations around AZLM at room temperature, with the locations varying trial to trial. The contribution of clathrin-independent endocytosis was more prominent when the number of stimulation pulses was large. The skewness of synaptophysin distribution in intracellular vesicles became smaller after addition of a clathrin inhibitor, which suggests that clathrindependent endocytosis concentrates synaptophysin. Ultrafast endocytosis was evident 3 immediately after stimulation only at near physiological temperature and was the predominant endocytosis when the number of stimulation pulses was small.